Projectuality and education, between learning objectives and political-cultural dynamics - Rosita Deluigi; Massimiliano Stramaglia (Firenze University Press, 2020)
The importance of knowing how to design is constantly and inevitably experienced in the concreteness of the territories. In the social field, the recipients are no longer to be considered mere receptors of interventions planned upstream, but active protagonists. In this situation, the educator assumes an eminently political role and adopts the socio-cultural animation framework, connecting individual projectuality and community planning. Finally, the article presents an analysis of the core contents of the degrees class L-19, identified, at the national level, through the research project Teco-D Pedagogia; some research paths and lines of contamination and implementation between researchers and professionals; various content proposals related to the training path of kindergarten and socio-pedagogical educators in order to the unavoidable, and sometimes neglected, theme of educational planning.   Per un'educazione progettuale, tra obiettivi formativi e dinamiche politico-culturali L'importanza del saper progettare si coniuga con la proposta di una centratura sui territori, nell'ambito dei quali i soggetti destinatari non sono più da considerarsi meri recettori di interventi progettati a monte, ma protagonisti attivi degli stessi. L'educatore, in siffatto frangente, assume un ruolo eminentemente politico e adotta l'idea-guida dell'animazione socio-culturale, così da connettere il piano della progettualità con quello della progettazione vera e propria. Si offrono, infine, delle analisi inerenti ai contenuti core della classe delle lauree L-19, individuati, a livello nazionale, attraverso il progetto di ricerca Teco-D Pedagogia; delle piste di ricerca e delle linee di contaminazione attuativa fra i teorici e i pratici; alcune proposte contenutistiche relative al percorso di formazione degli educatori di nido e socio-pedagogici in ordine al tema ineludibile, e talora trascurato, della progettazione educativa.